The Correlations between Language Barriers and Occupational Safety and Health Communication in Indonesia - Rojak, Octovianus Bin; Handayani, Yusnita (International Journal of Occupational Safety and Health, 2023)
Introduction: Miscommunication can cause accidents in workplaces due to the ineffective occupational safety and health (OSH) communication. There are many factors of ineffective OSH communication, one of which is the language barriers. Thus, this research aims to unveil the types of language barriers and its relation to the effectivity of OSH communication in Indonesia. Methods: A descriptive cross-sectional approach using a structured questionnaire was done in this research. The structured questionnaire survey was done among 102 workers in PT ABC, Indonesia. Spearman rho, a dedicated form of Pearson r, was used to determine the correlation between language barriers and effective OSH communication. Results: All of the types of language barriers except vernacular correlate positively, strongly and significantly to the effectivity of OSH communication (0.50 ≤ r ≤ 0.699, p-value < 0.05). Vernacular correlate positively, moderately, and significantly to the effectivity of OSH communication (r 0.497, p-value < 0.05). Conclusions: Based on the findings, OSH communication should be communicated accurately, clearly, and concisely in the language that everyone can understand.